Obstructive Hydrocephalus and Cardiomyopathy Secondary to Disseminated Protothecosis in a Boxer Dog - Anna Tauro; John Macri; Chris Gaudette; Christopher L. Mariani; Bonnie Brenseke (Case Reports in Veterinary Medicine)
Canine protothecosis is a rare disease caused by saprophytic unicellular achlorophyllous aerobic algae that are ubiquitous in the environment. We report a novel case of neurological and cardiological manifestations associated with disseminated protothecosis. An adult spayed female Boxer dog was presented with a 1-week history of anorexia, progressive central vestibular signs, and a Grade III/VI systolic heart murmur. Magnetic resonance (MR) imaging revealed obstructive hydrocephalus at the level of the mesencephalic aqueduct, while echocardiography and elevated troponin levels suggested an infiltrative cardiomyopathy. No obvious cause was identified. Cerebrospinal fluid (CSF) collection was not performed due to associated procedural risks. Despite receiving symptomatic treatment and maintaining stability for 3 weeks, the dog eventually suffered cardiorespiratory arrest. Postmortem examination revealed disseminated protothecosis, predominantly affecting the heart and brain. We recommend that in cases where the cause of obstructive hydrocephalus is unclear, especially when CSF collection is not feasible, a comprehensive diagnostic method should be implemented. This includes meticulous investigations to identify infected tissues, followed by sampling and performing cytology/histology and culture tests to confirm the presence of the algal organism. Early diagnosis may allow early treatment, although long-term prognosis remains largely unfavorable due to the absence of effective treatments.